A 3D Printed Device for Low Cost Neural Stimulation in Mice - Morrison, Taylor J.; Sefton, Elana; Marquez-Chin, Melissa; Popovic, Milos R.; Morshead, Cindi M.; Naguib, Hani E. (Frontiers in Neuroscience, 2019)
Electrical stimulation of the brain through the implantation of electrodes is an effective treatment for certain diseases and the focus of a large body of research investigating new cell mechanisms, neurological phenomena, and treatments. Electrode devices developed for stimulation in rodents vary widely in size, cost, and functionality, with the majority of recent studies presenting complex, multi-functional designs. While some experiments require these added features, others are in greater need of reliable, low cost, and readily available devices that will allow surgeries to be scheduled and completed without delay. In this work, we utilize 3D printing and common electrical hardware to produce an effective 2-channel stimulation device that meets these requirements. Our stimulation electrode has not failed in over 60 consecutive surgeries, costs less than $1 USD, and can be assembled in less than 20 minutes. 3D printing minimizes the amount of material used in manufacturing the device and enables one to match the curvature of the connector’s base with the curvature of the mouse skull, producing an ultra-lightweight, low size device with improved adhesion to the mouse skull. The range of the stimulation parameters used with the proposed device was: pulse amplitude 1-200 μA, pulse duration 50-500 μs and pulse frequency 1-285Hz.